Світовий досвід формування державної промислової політики - Дука, Анастасія Петрівна (My University, 2014)
У статті узагальнено світовий досвід реалізації державної промислової політики. Запропоновано шляхи трансформації моделі промислової політики в Україні для забезпечення прискореного розвитку на основі активізації інноваційних та інвестиційних процесів. Доведено, що програми модернізації обмежені досягненням цілей наздоганяючого розвитку і не здатні забезпечити розвиток економіки України на довгострокову перспективу. In the article global experience of the state industrial policy’s realization is summarized. The ways of the industrial policy model’s transformation in Ukraine for ensuring accelerated development on basis of intensification of innovation and investment processes are proposed. It is proved that the programs of the modernization are restrained by achievement of the overtaking development’s targets and are not capable to provide the long-term development of Ukrainian economy.
Keywords: кафедра економіки праці та менеджменту; промислова політика; модернізація; прискорений розвиток; досвід промислової політики; іndustrial policy; modernization; accelerated development; experience of the industrial policy